Patients profile of traumatic amputation: an analysis of factors that can help or prevent the treatment adherence - Castelli, Isabela (Archives of Business Research, 2021)
Amputee surgeries refer to the removal of totally or partial part of an organ. There are few illnesses that can lead to an amputation: cancer, diabetes, infections and traumas. We should stand out about the traumatic amputees’ patient’s profile: young, on working age and with no previously known disease. In the United States of America, are estimated 185.000 amputations per year which 45% are provoked for traumatic accidents. It’s estimated that by the year of 2050 the total number of amputees will reach about 3.6 million people. That makes the attendance and follow-up of amputees a public health issue. It is essential that an amputee patient be evaluated and monitored by a psychological professional. These study analysis 11 traumatic amputees and the factors that influenced adherence. The results show that social factors, type of amputation and use of drugs are the principal factors to be considered.